Symposium 3: Born into the Digital Age in the south of Africa: The reconfiguration of the “digital citizen” - Czerniewicz, Laura; Brown, Cheryl (Proceedings of the International Conference on Networked Learning, 2010)
Our previous research amongst South African university students showed opportunities in a divided and unequal context for digital democracy in the form of a mobile society. While computer divides are manifest amongst South African university students, cell phone access is ubiquitous. In the light of this, we explored students’ digital practices, especially in relation to learning. This paper adopts a qualitative approach to two cases - a mobile-centric and a computer-centric student respectively - and uses Bourdieu’s notions of objectified and embodied cultural capital as a theoretical frame to explore their differences and similarities, their convergences over time and their disparate histories. We describe the different types of objectified cultural capital available to each student and examine the processes of appropriation of embodied cultural capital respectively. We then explore the relationship between these different types of capital and their shaping of the students’ attitudes to and choices about using ICTs for learning. In particular we note the role that one type of objectified capital – the cell phone - has played in this relationship. The case studies surface complexities which need unravelling, and point to the research questions to be explored when grappling with participation in higher education in a digital age.